Disruption of pre-TCR expression accelerates lymphomagenesis in E2A-deficient mice - Engel, Isaac (National Academy of Sciences, 2002)
The helix–loop–helix proteins E47 and E12, which are encoded by the E2A gene, regulate several stages of T cell development. In addition, mice deficient for E2A are highly susceptible to thymic lymphoma. Here we report that the development of lymphoma in E2A-deficient mice did not require pre- and recombinase-activating gene expression. Rather, we found that, whereas illegitimate DNA rearrangement did not play a major role in the development of these lymphomas, defects that prevented pre-T cell antigen receptor expression tended to accelerate lymphomagenesis in E2A-deficient mice. These data and previous observations also provide insight into the role of Notch in lymphoma development. Specifically, we propose that Notch activation indirectly modulates E2A activity through induction of pre-Tα expression, ultimately leading to the development of lymphoma.